2020
DOI: 10.1021/acsphotonics.0c00294
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Nanoantennas for Strain Engineering in Atomically Thin Two-Dimensional Semiconductors

Abstract: Atomically thin two-dimensional semiconducting transition metal dichalcogenides (TMDs) can withstand large levels of strain before their irreversible damage occurs. This unique property offers a promising route for control of the optical and electronic properties of TMDs, for instance, by depositing them on nanostructured surfaces, where position-dependent strain can be produced on the nanoscale. Here, we demonstrate strain-induced modifications of the optical properties of mono-and bilayer TMD WSe 2 placed on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 70 publications
2
38
0
Order By: Relevance
“…Despite these promising first results, the physical mechanisms that govern changes in the TMD emission as they are placed in proximity of the nanoresonators need to be understood. In addition to the targeted modification of the local electric field due to the resonator, several other mechanisms such as strong local strain induced by the resonator [22] and changing optical dipole orientation with respect to the detection contribute to brightening and change in directivity of the emission.…”
mentioning
confidence: 99%
“…Despite these promising first results, the physical mechanisms that govern changes in the TMD emission as they are placed in proximity of the nanoresonators need to be understood. In addition to the targeted modification of the local electric field due to the resonator, several other mechanisms such as strong local strain induced by the resonator [22] and changing optical dipole orientation with respect to the detection contribute to brightening and change in directivity of the emission.…”
mentioning
confidence: 99%
“…Contrary to other group-VI TMDs, tensile strain in WSe 2 results in the lowering of the conduction band (CB) minimum and the rise of the valence band (VB) maximum, as shown in Fig. 3a, both located at the K points in the momentum space 8,35 . This creates an energy landscape where a very small fraction of the 2D exciton population may be captured into such 0D centers, giving rise to nonclassical light emission from confined states, at photon energies lower than that of both bright and dark excitons in unstrained WSe 2 .…”
Section: Resultsmentioning
confidence: 90%
“…1f. In what follows, we focus on GaP dimer nanoantennas, as these provide pronounced and interesting photonic effects, as was shown in our preliminary work 7,8 . On the other hand, less studied GaP monomers (single nanopillars) may also be useful for achieving SPE positioning and improved PL in WSe 2 monolayers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter being independent of the Au NPs optical density, the absorption of the MoSe 2 PL emission by the Au NPs can be ruled out to account for the observed PL quenching of MoSe 2 . Several studies [16,[36][37][38][39][40][41][42][43][44] showed that the strain imposed by the metal NPs to the TMD layer may strongly modify its electronic band structure and can be responsible for a strong quenching of the PL emission. In particular, tensile strain may induce a direct-to-indirect band gap transition [37,41,42] which leads to a red shift of the PL peak and to a drastic decrease of the PL intensity [38,39,42,43].…”
Section: Resultsmentioning
confidence: 99%